2018
DOI: 10.1007/s40519-018-0486-1
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption after laparoscopic sleeve gastrectomy: 1-year results

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…Being at risk for alcohol use disorder was reported by only 1.9% of the current sample, which is much lower than in the general population (19.0%, Gomes de Matos, Atzendorf, Kraus, & Piontek, 2016). Comparisons with past preoperative samples revealed inconsistent results, with some previous studies documenting rates close to that of the current sample (2.7%, Coluzzi, Iossa, Spinetti, & Silecchia, 2018;2.2%, de Amorim, de Souza, Nascimento, Maio, & Burgos, 2015) and others higher rates (7.6%, King et al, 2017;King et al, 2012). Also, the proportion of patients being at risk for nicotine use disorder was lower (6.0%) than in the general population (9.5%, Gomes de Matos et al, 2016).…”
Section: Discussioncontrasting
confidence: 92%
“…Being at risk for alcohol use disorder was reported by only 1.9% of the current sample, which is much lower than in the general population (19.0%, Gomes de Matos, Atzendorf, Kraus, & Piontek, 2016). Comparisons with past preoperative samples revealed inconsistent results, with some previous studies documenting rates close to that of the current sample (2.7%, Coluzzi, Iossa, Spinetti, & Silecchia, 2018;2.2%, de Amorim, de Souza, Nascimento, Maio, & Burgos, 2015) and others higher rates (7.6%, King et al, 2017;King et al, 2012). Also, the proportion of patients being at risk for nicotine use disorder was lower (6.0%) than in the general population (9.5%, Gomes de Matos et al, 2016).…”
Section: Discussioncontrasting
confidence: 92%
“…A large multi-institutional study by Ibrahim et al showed an increase in alcohol use after sleeve gastrectomy and identified higher educational level and higher household income as predisposing factors to this change [8]. In contrast, a study by Coluzzi et al [9] showed a decrease of alcohol use 1 year after sleeve gastrectomy and attributed it to strict nutritional follow-up after surgery. The "addiction transfer" model has been implicated as one mechanism underlying a rise in alcohol misuse after WLS in which obese patients whose eating is driven by hedonic response to food substitute substances such as alcohol in lieu of food [5,10].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that alcohol misuse after RYGB may be related to reduced GHSR control of the VTA dopaminergic system. Similar animal models have been developed for VSG[ 33 , 34 ]. In contrast to RYGB models, mice with VSG demonstrated reduced alcohol seeking behavior compared to control mice.…”
Section: Pathophysiology Of Alcohol Use Disorder After Bariatric Surgerymentioning
confidence: 99%